Hubungan Lama Pemakaian Kontrasepsi Suntik Kombinasi Dengan Kadar Glukosa Darah Di Bpm “E” Kecamatan Purwosari, Pasuruan - Sri Rahayu; Siti Sundari; Erni Widiyani (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2015)
Injectable is one of the most widely used contraceptives in Indonesia. Injectable contraceptive often causes the changes in blood glucose levels because it contains a steroid hormone with low anti-insulin. The use in the long term can even cause pancreatitis. Hormones in injectable contraceptive have opposite work against insulin. Insulin resistance causes pancreas to increasingly work harder to produce insulin. Over time the pancreas will not be able to function optimally and will have an impact on blood glucose levels. The objective of this study was to determine the relationship of the length of injectable contraceptive use to blood glucose levels among combined injectable acceptors. This study used cross sectional study design. The source of data was primary data with the respondents combined injectable acceptors in Privately Practising Midwife